From Firm Productivity Dynamics to Aggregate Efficiency - Lopez-Martin, Bernabe (Published by Oxford University Press on behalf of the World Bank, 2019)
The author constructs a quantitative framework to evaluate how financial constraints can reduce productivity growth at the firm level and result in lower aggregate productivity. The author considers a model where firms are able to invest in innovation in order to increase their productivity, or knowledge capital. This investment is a costly and uncertain enterprise. As the capacity to obtain external funds is diminished, resources allocated to this effort will be reduced due to different mechanisms at work. First, the return of this investment in the case of success may be diminished by the inability to quickly increase production capacity if the credit necessary to do so is scarce (i.e., if entrepreneurs cannot rent the optimal level of physical capital). Second, financial constraints reduce profits obtained by entrepreneurs and therefore the amount of assets they are able to accumulate in every period. Finally, financially underdeveloped economies will be characterized by a lower average ability of entrepreneurs. This is due to the lower equilibrium wage in the economy, which results in a larger mass of individuals opting to set up firms. In the margin, these individuals tend to have lower ability to manage a firm and relatively low prospects of generating firm productivity growth through innovation.